Interventions on Improving Medication Adherence in Malaysia: A Mini Review - Ting, Chuo Yew; Zaidi Adruce, Shahren Ahmad; Loo, Shing Chyi; Ting, Hiram; Tnay, Jessie (InPharm Association, 2019)
Medication non-adherence is a global issue. Past review on the interventions to improve medication adherence provided little practical implications for healthcare professionals and policy makers in Malaysia, due to the substantive differences across studies. Hence, this review attempted to evaluate the interventions on improving medication adherence conducted in Malaysia, to generate some insights and recommendations for future interventions. Method: Search of past literatures from Google Scholar, PubMed, MEDLINE, EBSCO, PsycINFO, CINAHL (via EBSCO) with search strategy: “medication adherence or medication compliance” [Mesh] AND “intervention” [Mesh] AND “Malaysia” AND English [lang- Lang] was conducted on September 28, 2016. The framework of judging methodological quality used by Zwikker and colleagues was employed. Results and Discussion: A total of 28 articles were identified. Studies which were not conducted using Malaysia population, not measuring medication adherence, without intervention on medication adherence, non-prospective and non-experimental design were omitted. Hence, 9 articles were retained for further evaluation. Eight out of the nine prospective randomized controlled studies were found to be low-quality studies. Overall, interventions that were pharmacist led, physician led, adoption of automated text messaging reminder and improvised medication labelling were found to be effective. Conclusion: This review provides valuable insights on contemporary interventions to improve medication adherence conducted in Malaysia. It is suggested that multifaceted approach with involvement of different healthcare professionals should be encouraged to synergize the strengths of each profession and to further enhance the effectiveness of interventions.